(untitled) (Gestionar: revista de empresa y gobierno, 2021)
The study presents the results obtained from an archaeological survey proposing a tourism development plan in the Huertas sector of the peasant community of Huata Quita, district of Cabanillas, department of Puno, where the Inka Pakarita archaeological center is located, since there is evidence of three Funeral Chullpas with galleries of up to three floors belonging to the Pre-Inca culture of Tiahuanaco, where human bones and numerous seed roots (corn, wheat, quinoa) were found, the objective of the study was to encourage the authorities to be interested in the construction of a tourist center to promote and encourage local and national tourism to attract economic resources and promote community development so that there is a management of tourism and thus promote knowledge of archaeological sites. The methodology is purely descriptive; the archaeological prospecting was applied accentuated in the propositional intention. The results reflected the lack of interest and the little value to the archeology of the governmental authorities.